2016
DOI: 10.1017/s0021932016000341
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index and Self-Employment in South Korea

Abstract: This study assesses differential labour performance by body mass index (BMI), focusing on heterogeneity across three distinct employment statuses: unemployed, self-employed and salaried. Data were drawn from the Korean Labor and Income Panel Study. The final sample included 15,180 person-year observations (9645 men and 5535 women) between 20 and 65 years of age. The findings show that (i) overweight/obese women are less likely to have salaried jobs than underweight/normal weight women, whereas overweight/obese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
0
5
0
1
Order By: Relevance
“…It has been reported that obese people earn less, are less likely to be hired, or are more likely to remain unemployed [14,15]. Further studies also indicate that obese individuals are less likely to be sorted into jobs that have socially desirable work profiles, such as earning a high salary, positioning in a professional or semi-professional sector, and receiving benefits of high quality in both monetary and non-monetary aspects [16].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that obese people earn less, are less likely to be hired, or are more likely to remain unemployed [14,15]. Further studies also indicate that obese individuals are less likely to be sorted into jobs that have socially desirable work profiles, such as earning a high salary, positioning in a professional or semi-professional sector, and receiving benefits of high quality in both monetary and non-monetary aspects [16].…”
Section: Introductionmentioning
confidence: 99%
“…Household endowments could directly influence the labor market outcomes by influencing the willingness to be employed, nature of employment sought, and the effort put forth in employment activities (Hurst & Lusardi, 2004; Kochar, 1995). As height has been shown to influence income (Rietveld, Hessels, & van der Zwan, 2015) and weight and obesity levels have been shown to influence labor market outcomes (Han & Kim, 2016), we included these physiological measures in our controls. Similarly, as health insurance has recently been shown to impact self-employment outcomes, we included a dummy variable for whether the respondent had private health insurance (Gumus & Regan, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Laitinen et al reported a higher risk of obesity after longer periods of unemployment in women [ 3 ]. In a large Korean cross-sectional study, women with overweight or obesity showed a higher risk of unemployment than normal- or underweight women [ 13 ].…”
Section: Introductionmentioning
confidence: 99%